Influências e confluências do uso do suporte de escrita digital na alfabetização de crianças do 1º ano do primeiro ciclo - Julianna Silva Gloria (2011)
This research proposes to examine the implications of computer use and their contributions in the initial period of literacy, focusing on aspects of literacy and digital literacy that develop in the area of public schools in Belo Horizonte with children six years. The theoretical references were based on studies of the field educational and sociohistorical psychology related to literacy (Magda Soares), with the internalization of knowledge (L. Vygotsky) and the relations between cognition, signification and interaction (Ana Luiza B. Smolka). On the connection between screen writing and conceptual development of the writing system, use the research of Claudia Molinari and Emília Ferreiro. From the linguistic point of view, we used studies of genre, especially developed for Marcuschi. In field studies on digital culture and the written culture, the transformation of support/ instruments and its interference in the relationship between readers / writers with such changes have been in corporated concepts used by Roger Chartier, Pierre Lévy, Jack Goody and Antonio CastilloGomez. The research also drew upon various studies on usability, multimodality modeling support and historical studies of support / writing instruments in school. The adopted principles of qualitative research with the proposition of accompanying children aged 6 years in the computer lab in various situations of writing and reading activities on the computer screen. The research used observation procedures, annotation, filming and interviews. The analysis of interactions between children themselves and with the writing / reading on screen, as well as interviews, demonstrated that the use of computer as an instrument to produce writing had a special meaning for the children involved in research; they learned to write to communicate through text genres, including virtual media with and without the full mastery of alphabetic writing; used multimodality typical features of the screen to give an account of writing tasks; expressed their representations of handwriting and digital writing, revealing that make distinctions according to the use and according toits effort in the appropriation of actions needed for reading and writing in different support